Students' Motivation under the Study of Foreign Languages in a Pharmaceutical University - I. V. Arkhipova; G. A. Rozhkov; S. V. Pristupa; E. O. Sergopoltseva; A. P. Tumanova (Дискурс)
Introduction. The authors of the research aimed to determine the level of students' interest in foreign languages, leading motives, as well as the presence of difficulties arising under the study of a foreign language. The importance of motivation in the process of learning foreign languages in a non-linguistic university is emphasized.Methodology and sources. The authors of the research describe the questionnaire survey and analysis of the results obtained in its course. This research involved 267 students of 1–2 courses of the Pharmaceutical Faculty of the Saint Petersburg State Chemical and Pharmaceutical University.Results and discussion. The modern pharmaceutical industry is actively developing, which implies the exchange of technology and knowledge between representatives of different countries. Most pharmaceutical companies have subsidiaries all over the world. A demanded employee needs to have the skill of effective intercultural dialogue in this professional field. In recent decades, the role of foreign languages has increased all over the world, and the necessity to know them is generally recognized.Conclusion. The paper has shown the level of the development of motivation for learning a foreign language by students in order to further increase the level of development of their motivation in the learning foreign languages. The conclusion was made that student motivation stands out as one of the main factors in achieving success in both educational and professional activities and, therefore, should be a priority for all teachers.